TRANSFORMATION OF ISLAMIC RELIGIOUS EDUCATION IN HIGHER EDUCATION IN THE DIGITAL AND TECHNOLOGICAL ERA - Agustian Zen; Kresnawidiansyah A; Mohamad Sarip; Zulhimma; Fahrina Yustiasari Liriwati (CV. ADIBA AISHA AMIRA, 2023)
This paper looks at how Islamic religious education in higher education has changed as a result of digital and technological advancements. It looks at how Islamic religion education uses interactive multimedia and online learning platforms, highlighting how these technologies improve education quality and make learning materials more accessible. The use of mobile applications and digital technology for distance learning in Islamic religious education are also discussed in this paper. It acknowledges the difficulties associated with implementing digital technology, such as limitations in infrastructure, faculty and student readiness, and the significance of ethical and secure technology use. To overcome these obstacles, the paper suggests approaches like infrastructure planning, faculty training, and policy development. It concludes that incorporating digital technology can foster interactive learning environments, increase resource accessibility, and enhance the quality of education. The effectiveness of various digital innovations and the factors that influence the adoption of technology in religious education require additional investigation. However, additional research is required to determine the factors that influence the adoption of technology in religious education and to assess the efficacy of various innovations in digital technology.